2000
DOI: 10.1016/s0022-2275(20)32369-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal sphingomyelins are precursors for selected stratum corneum ceramides

Abstract: Epidermal ceramides (Cer) comprise a heterogeneous family of seven species, including two unique -hydroxylated Cer, that are key components of the stratum corneum (SC) intercellular lamellar membranes responsible for the epidermal permeability barrier. Although both glucosylceramide (GlcCer) and the phospho-sphingolipid sphingomyelin (SM) are potential precursors of SC Cer, based on reported chemical structures of epidermal GlcCer and SC Cer, it is assumed that all major subfractions of SC Cer are generated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(46 citation statements)
references
References 72 publications
4
42
0
Order By: Relevance
“…This results in a considerable deficiency in the acid, lipid, and enzyme constituents of the SC, leading to a defective barrier function (Mecheleidt et al, 2002). An increase in sphingomyelin deacylase activity is also associated with AD and results in a decreased production of ceramide (Hara et al, 2000).…”
Section: Structure Of the Epidermal Barriermentioning
confidence: 99%
See 1 more Smart Citation
“…This results in a considerable deficiency in the acid, lipid, and enzyme constituents of the SC, leading to a defective barrier function (Mecheleidt et al, 2002). An increase in sphingomyelin deacylase activity is also associated with AD and results in a decreased production of ceramide (Hara et al, 2000).…”
Section: Structure Of the Epidermal Barriermentioning
confidence: 99%
“…Conversely, cathepsin LZ and cathepsin D have an acidic pH optimum (Horikoshi et al, 1999;Bernard et al, 2003). The lipid-generating enzymes, b-glucocerebrosidase and sphingomyelinase, also exhibit low acid pH optimum (Holleran et al, 1993;Jensen et al, 1999;Schmuth et al, 2000;Uchida et al, 2000). Taken together, the pH gradient across the epidermis is very important in regulating desquamation and the generation of the lamellar matrix.…”
Section: The Acid Mantlementioning
confidence: 99%
“…Low levels of GluCer and ceramide in atherosclerosis-prone mice led to skin inflammation and hair discoloration and loss (Bedja et al, 2018). Prior studies demonstrated that all molecular species of stratum corneum ceramides are derived from GlcCer (Uchida et al, 2000;Hamanaka et al, 2002). In addition, GlcCer also prevents dehydration of the stratum corneum and repaired the barrier function of skin.…”
Section: Glccers Are Important For the Barrier Function Of Skin As Moisturizing Ingredients Or Dietary Supplementsmentioning
confidence: 99%
“…During activation of sphingomyelinase in response to stimuli; for example, cytokines and oxidative stressors [1,2], SM is hydrolyzed to ceramide (Cer), which in turn serves as a lipid regulator of cellular functions [3,4]. In epidermis, Cer produced from SM and glucosylceramides (GlcCers) at the transition from the stratum granulosum (SG) to the stratum corneum (SC) are constituents of the epidermal permeability barrier, which is required for mammalian survival in a terrestrial environment [5][6][7]. SM synthase (SMS)1 and SMS2, which are distributed in the trans-Golgi and plasma membranes, respectively, synthesize SM [3].…”
Section: Introductionmentioning
confidence: 99%